DINAMIKA PASANG AKSARA BALI : SEBUAH KAJIAN HISTORIS SISTEM EJAAN - Ida Made Windya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Balinese, in addition to being written in Latin letters, is also written in Balinese script.Every alphabet has its code called spelling. Language inheritance carries spelling inheritance.Until now in the Balinese script writing system two spellings have been applied, namely thespelling of Purwadresta and the spelling of Schwartz. Each spelling has its own provisionswhich until now are still inherited. The Balinese script used to write the Sanskrit, Old Javanese,and Balinese languages up to now has experienced the development or dynamics from the verybeginning of its existence. The development of Balinese script pairs generally still leads tofunctionalization, inheritance of values, and cultural preservation.